Facts and fears [compact disc, unabridged] : hard truths from a life in intelligence - Clapper, James R. (James Robert), 1941-; Brown, Trey (Penguin Audio, 2018)
When he stepped down in January 2017 as the fourth United States Director of National Intelligence, James Clapper had been President Obama's senior intelligence advisor for six and a half years, longer than his three predecessors combined. He led the US Intelligence Community through a period that included the raid on Osama bin Laden, the Benghazi attack, the leaks of Edward Snowden, and Russia's influence operation on the 2016 U.S election. Clapper traces his career through five decades of national intelligence operations, the growing threat of cyberattacks, his relationships with Presidents and Congress, and the truth about Russia's role in the presidential election. He describes, in the wake of Snowden and WikiLeaks, his efforts to make intelligence more transparent and to push back against the suspicion that Americans' private lives are subject to surveillance.